Telaah Kritis Expectancy Theory Victor Harold Vroom - Lina Anatan (Jurnal Manajemen Maranatha, 2010)
Expectancy theory has emerge as the dominant process theory of motivation, originally developed by Vroom is a theory explaining the process individual use to make decision on a various behavioral alternatives. The motivational force for a behavior, action, or task is a function of three distinctive perceptions: expectancy, instrumentality, and valance. The theory contains of two models: for the precition of valance of an outcome, and the other for the prediction of force toward behavior. It provides a general framework for assessing, interpreting, and evaluating employee behavior in learning, decision making, attitude formation, and motivation.Keywords: expectancy theory, expectancy, instrumentality, valance